Modelling of crystallization process using the interval boundary element method - Majchrzak, Ewa; Piasecka-Belkhayat, Alicja (Computer Assisted Methods in Engineering and Science, 2007)
The mathematical model of solidification process can be formulated using the macro or micro-macro approach. In this paper the second generation model (micro-macro one) is considered. The driving force of crystallization is the local and temporary undercooling below solidification point Tcr . The nucleation and nuclei growth are proportional to the second power of undercooling. Formulas determining the phenomena previously mentioned contain coefficients called the nucleation coefficient and nuclei growth one. These coefficients are assumed to be interval values. For above assumptions the problem has been solved bymeans of interval boundary element method. In the final part of the paper the results of computations are shown.